Moving to business - changes in physical activity and sedentary behavior after multilevel intervention in small and medium-size workplaces - Minna Aittasalo; Matleena Livson; Sirpa Lusa; Ahti Romo; Henri Vähä-Ypyä; Kari Tokola; Harri Sievänen; Ari Mänttäri; Tommi Vasankari (BMC, 2017)
Abstract Background Regular physical activity (PA) promotes and excessive sedentary behavior (SB) deteriorates health. Yet the Finnish working-aged population spends most of the day sitting. A 1-year Moving To Business (MTB) -intervention supported small and medium-size workplaces to combat sedentariness. This paper reports the changes in employees' PA and SB from before MTB (baseline) to 1 year after baseline (follow-up). Methods Twelve workplaces with a total of 396 employees participated. Each workplace nominated a team to promote PA and reduce SB at organizational, working unit and employee level. The teams were mentored regionally through meetings, workshop and tools. Changes in PA and SB were assessed with a questionnaire and an accelerometer. Wald Confidence Interval (Cl) for a difference of proportions with matched pairs was used in the questionnaire data (%-points with 95% CI) and linear mixed model in the accelerometer data (minutes and % of wear-time with 95% CI). Results The mean age of the respondents to the questionnaire (N = 296; 75%) was 42.6 (SD 10.9), 64% were women, 95% had some education after high school, 74% worked in the day shift, 71% did sedentary work and 51% were overweight. The mean number of actions implemented in the workplaces was 6.8 and the multilevel approach was fully applied in 6 workplaces. Based on the questionnaire the time spent in SB decreased from baseline to follow-up 16% (95% CI −29 to −3) in total and 22% (−41 to −3) at work. The accelerometer showed daily increases of 33.7 min (15.3 to 52.1) and 6.8% (3.1 to 10.4) in total PA, 30.9 min (15.3 to 46.5) and 6.1% (2.9 to 9.2) in light PA and 673 (209 to 1139) more steps at work. Daily SB at work decreased 44.9 min (−68.0 to −21.8) and 7.6% (−11.9 to −3.2). Daily leisure PA declined 11.0 min (−24.9 to 2.9) and 3.2% (−6.2 to −0.2). Number of levels or actions had no effect on changes. Conclusions Employees' PA increased and SB reduced at work during the intervention. At the same time leisure PA decreased slightly. Workplaces can achieve meaningful changes in employees' PA and SB if assisted systematically. Controlled studies are needed to confirm the present findings. Trial registration NCT01999205 , registration date 11/01/2013.